Interpersonal and Metapersonal Self-Regulation of Al-Quran Memorizer Santri at Elementary School Level - Muh. Shaleh; Kharis Sulaiman Hasri; Faizah Binti Awad (STAI Hubbulwathan Duri, 2021)
This article aims to examine the interpersonal and metapersonal self-regulation of students memorizing the Qur'an at the elementary school level. This research adopted a phenomenological case study research design. Six students, five parents of students, and one teacher were recruited for data collection. Interviews, observation and documentation were conducted to obtain data. The results report that students' interpersonal self-regulation was carried out by preaching to their peers by reprimanding their friends or siblings. They try to regulate themselves to be able to harmonize their thoughts, words, and actions in the form of a polite attitude. They also strive to manage the existing environment in order to support the achievement of the goals that have been set. Environmental management is an effort to invite other friends to use their free time to use memorization. The metapersonal self-regulation is conducted by seeking the pleasure of Allah. However, the students who memorize the Qur'an at the elementary school level at the Tadabbur Al-Qur'an House have not been able to feel certain mental activities that can facilitate the process of memorizing the Qur'an. Among the inner activities that are carried out are certain prayers, especially to get help in the hereafter.